Comparative Studies On The Percentage Yield Of Soft Cheese Produced From Various Animals’s Milk Using Different Coagulants - Oluwatoyin Modupe Aladejana (Journal of Environmental Science, Toxicology and Food Technology, 2020)
Abstract The comparative study of the percentage yield of soft cheese produced from different animal’s milk was done. Soft cheese was produced from cow, sheep and goat using six different coagulants of plant origin: Calotropis procera, Carica papaya, lemon juice and steep water from maize, millet and sorghum. The objective of this study was to compare the yield of the soft cheese produced from these coagulants. The result revealed that for cow milk, Calotropis procera had the highest percentage yield (27.3%) while steep water from millet had the lowest percentage yield (5.1%). For sheep milk, Calotropis procera also had the highest percentage yield (25.6%) while steep water from maize had the lowest percentage yield (3.8%). However, for goat milk, Carica papaya had the highest percentage yield (23.3%) while steep water from millet had the lowest percentage yield (7.4%). In conclusion, this study suggests that soft cheese from goat milk can be an alternative to the commonly used cow milk in terms of percentage yield. Coagulants such as Carica papaya is a better alternative to the commonly used Calotropis procera in cheese making industry.